2020
DOI: 10.3390/rs12162542
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation and Consistency Comparison of UAV Multispectral Minisensors

Abstract: In recent years, the use of unmanned aerial vehicles (UAVs) has received increasing attention in remote sensing, vegetation monitoring, vegetation index (VI) mapping, precision agriculture, etc. It has many advantages, such as high spatial resolution, instant information acquisition, convenient operation, high maneuverability, freedom from cloud interference, and low cost. Nowadays, different types of UAV-based multispectral minisensors are used to obtain either surface reflectance or digital number (DN) value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 60 publications
0
31
1
2
Order By: Relevance
“…Recently, a study on accurately evaluating the radiometric quality of UAV imagery is underway, which will reduce the analytical potential of images and eliminate interference, which can distort the results of remote sensing analysis [19,47]. Since reflective data of the research area can be obtained directly after using sequoia image and processing it, it was reported that errors of spectral indices are correlated with a way of calibrating a level of radiation in the case that spectral indices are calculated using the reflective data of spectral indices equation [49].…”
Section: Uav Data Acquisition and Image Processingmentioning
confidence: 99%
“…Recently, a study on accurately evaluating the radiometric quality of UAV imagery is underway, which will reduce the analytical potential of images and eliminate interference, which can distort the results of remote sensing analysis [19,47]. Since reflective data of the research area can be obtained directly after using sequoia image and processing it, it was reported that errors of spectral indices are correlated with a way of calibrating a level of radiation in the case that spectral indices are calculated using the reflective data of spectral indices equation [49].…”
Section: Uav Data Acquisition and Image Processingmentioning
confidence: 99%
“…The focal length of the P4M camera is 5.74 mm, image size is 1600 × 1300 pixels, and sensor size is 4.87 × 3.96 mm [38]. The P4M demonstrated good accuracy, yield, and consistent data generation [39]. The flight plan for automatic image acquisition was programmed with the DJI Ground Station Pro application [40].…”
Section: Uav Image Acquisition and Processingmentioning
confidence: 99%
“…The P4M camera has a focal length of 5.74 mm, a sensor size of 4.87 × 3.96 mm, and a global 2 MP shutter. Similar to other UAV-mounted multispectral cameras (e.g., Parrot Sequoia), the P4M demonstrates good accuracy and consistent data generation in terms of spectral reflectance and vegetation index acquisition [50] and is capable of obtaining the multispectral and RGB image simultaneously.…”
Section: Uav Image Acquisition and Processingmentioning
confidence: 98%